PENGARUH MEDIA PEMBELAJARAN MONOPOLY EDUCATION TERHADAP HASIL BELAJAR PKN SISWA KELAS IV DI UPT SD NEGERI 3 BATANG - Hawaliaa, Reski; Suardi; Gustaf Said, Try (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main problem addressed in this study is the low learning outcomes in Civics (PKn) among students, which stem from unengaging teaching methods and limited interaction. The aim of this research is to investigate the effect of using Monopoly Education media on the Civics learning outcomes of fourth-grade students at UPT SD Negeri 3 Batang. This study employed a quantitative approach using a one-group pretest-posttest experimental design. The sample consisted of 20 students. Data were collected through tests, observations, and documentation. Data analysis was conducted both descriptively and inferentially using a paired sample t-test. The results of the study indicated a significant improvement in learning outcomes after the intervention, as evidenced by the difference between pretest and posttest scores and a significance value of 0.001 (p < 0.05). Additionally, students showed increased active participation, self-confidence, and understanding of civic values. In conclusion, Monopoly Education was found to be effective in enhancing both students' Civics learning outcomes and their positive attitudes toward the subject. This study contributes to the development of innovative game-based learning media as an alternative strategy to improve the quality of civic education in elementary schools.